A study on the association of sexual factors and personal hygiene between couples in relation to cervical changes in pap smear - Dhalliwal, Ranjit Singh (2006)
OBJECTIVE: This study was conducted to determine the association of sexual factors and personal hygiene between couples in relation to cervical changes in Pap smear. METHODOLOGY: This multi centre cross sectional study was conducted in the Obstetric and Gynaecology Clinic of Hospital Universiti Sains Malaysia, Hospital Kota Bharu and Hospital Kuala Terengganu from June 2004 till May 2005. A total of 99 couples who fulfilled the criteria were interviewed and the Pap smear performed on the female spouse. Their sexual habits and personal hygiene in relation to cervical changes in Pap smear were then compared and analysed using SPSS Version 12.0 RESULTS: There were 55 (55.6%) of female respondents found to have reactive cervical changes in Pap smear. The degree of inflammatory changes were 33 (60%) mild, 13 (23.6%) moderate and 9 (16.4%) severe features. Three percent (3%) of the cervical smears exhibit organisms (trichomonas, candidiasis and HPV infections) and 14.1 % had per vaginal discharge. There were 31 (31.3%) from both female and male respondents who had early sexual activity «20 years). There were three male respondents whom had engaged in coitus before the age of 16 years. Sixty-eight percent (68%) of couples had coitus two to three times per week. There were only 7 (7.1 %) female respondents whom had more than two sexual partners (divorcee and remarried) and only one male respondent whom engagaed with sexual workers. Among the males, 87 patients (87.9%) had good genital hygiene and 95 patients (96 % ) practiced the habit of genitalia washing after sexual intercourse. There were 86 males (86.9%) who were circumcised. There were 88 (88.9%) females who practiced the habit of genital wash prior to intercourse. CONCLUSION: From the statistical analysis, there was no significant association of cervical changes in relation to the age of fITst intercourse among the male and female spouses, the number of sexual partners among female participants, the frequency of sexual activity among female participants, male of whom had sex with multiple sexual partners or sexual workers, the practice of applying condom, the status of circumcision, washing genitalia before or after intercourse in both couples and the status of genital hygiene.